Community engagement interventions for communicable disease control in low- and lower- middle-income countries: evidence from a review of systematic reviews - K. Questa; M. Das; R. King; M. Everitt; C. Rassi; C. Cartwright; T. Ferdous; D. Barua; N. Putnis; A. C. Snell; R. Huque; J. Newell; et al. (BMC, 2020)
Abstract Background Community engagement (CE) interventions include a range of approaches to involve communities in the improvement of their health and wellbeing. Working with communities defined by location or some other shared interest, these interventions may be important in assisting equity and reach of communicable disease control (CDC) in low and lower-middle income countries (LLMIC). We conducted an umbrella review to identify approaches to CE in communicable disease control, effectiveness of these approaches, mechanisms and factors influencing success. Methods We included systematic reviews that: i) focussed on CE interventions; ii) involved adult community members; iii) included outcomes relevant to communicable diseases in LLMIC; iv) were written in English. Quantitative results were extracted and synthesised narratively. A qualitative synthesis process enabled identification of mechanisms of effect and influencing factors. We followed guidance from the Joanna Briggs Institute, assessed quality with the DARE tool and reported according to standard systematic review methodology. Results Thirteen systematic reviews of medium-to-high quality were identified between June and July 2017. Reviews covered the following outcomes: HIV and STIs (6); malaria (2); TB (1); child and maternal health (3) and mixed (1). Approaches included: CE through peer education and community health workers, community empowerment interventions and more general community participation or mobilisation. Techniques included sensitisation with the community and involvement in the identification of resources, intervention development and delivery. Evidence of effectiveness of CE on health outcomes was mixed and quality of primary studies variable. We found: i) significantly reduced neonatal mortality following women's participatory learning and action groups; ii) significant reductions in HIV and other STIs with empowerment and mobilisation interventions with marginalised groups; iii) significant reductions in malaria incidence or prevalence in a small number of primary studies; iv) significant reductions in infant diarrhoea following community health worker interventions. Mechanisms of impact commonly occurred through social and behavioural processes, particularly: changing social norms, increasing social cohesion and social capacity. Factors influencing effectiveness of CE interventions included extent of population coverage, shared leadership and community control over outcomes. Conclusion Community engagement interventions may be effective in supporting CDC in LLMIC. Careful design of CE interventions appropriate to context, disease and community is vital.